Team-RUP: agent-based simulation of team behaviour in software development organisations. (1st October 2007) - Yilmaz, Levent; Phillips, Jared
This paper presents a simulation study that explores the effects of team behaviour on the efficiency and effectiveness of software development organisations that pursue incremental and iterative processes such as Rational Unified Process (RUP). The research vehicle is an agent-based model that organises teams according to the degree of autonomy in collaboration and the degree of concurrency in coordination, resulting in distinct team archetypes. We present the insights gained about the effectiveness and efficiency of team archetypes in response to various levels of task complexity and stability, as well as team size and workload factors.